Magneto-transport and magneto-dielectric anomalies in Co doped iron oxide thin films – Microwave assisted sol-gel route - Sidra Khalid; Saira Riaz; Aseya Akbar; Zaheer H. Shah; Zohra N. Kayani; Shahzad Naseem (Journal of Saudi Chemical Society)
Use of microwave (MW) energy as an alternate to high temperature treatment during material synthesis is gaining much attention as it offers the advantages of being faster and economical than other heating methods. A comprehensive study of structure, magnetization, and polarization behaviour of Cobalt (Co) doped Fe3O4 thin films, prepared by means of microwave assisted sol–gel method is performed. Co doped (0-10 wt%) sols are prepared after irradiating them at MW power of 1000 W. Phase analysis is confirmed using XRD where Fe3O4 phase persisted with Co concentrations of 0-6 wt%. Higher concentration results in the appearance of cobalt oxide phase. Magnetic and transport properties are strongly affected by the presence of Co ions. Co doped Fe3O4 films show anisotropic behaviour with high saturation magnetization obtained for 6 wt% Co doped Fe3O4 thin films, i.e. ∼ 125 emu/g. Verwey transition is observed for thin films with low dopant concentration while no sharp transition in magnetization behaviour is observed for higher dopant concentration. High frequency anomaly in dielectric analysis is observed at high frequencies for Co doped Fe3O4 thin films. Negative values of magneto-dielectric coefficient show coupling of magnetic and dielectric behaviour at room temperature.